2015
DOI: 10.18632/oncotarget.4347
|View full text |Cite
|
Sign up to set email alerts
|

Development and exploitation of a novel mutant androgen receptor modelling strategy to identify new targets for advanced prostate cancer therapy

Abstract: The persistence of androgen receptor (AR) signalling in castrate-resistant prostate cancer (CRPC) highlights the unmet clinical need for the development of more effective AR targeting therapies. A key mechanism of therapy-resistance is by selection of AR mutations that convert anti-androgens to agonists enabling the retention of androgenic signalling in CRPC. To improve our understanding of these receptors in advanced disease we developed a physiologically-relevant model to analyse the global functionality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Darolutamide also exhibited strong antagonism for several AR mutants for which other antagonists had only reduced activity. A prime example is the AR W742C/L forms which are stimulated by bicalutamide, thus activating an androgenic gene expression program resembling that of an AR agonist . Here we show that darolutamide remained a strong antagonist whereas enzalutamide and apalutamide had only reduced antagonist properties for these AR mutants.…”
Section: Discussionmentioning
confidence: 68%
“…Darolutamide also exhibited strong antagonism for several AR mutants for which other antagonists had only reduced activity. A prime example is the AR W742C/L forms which are stimulated by bicalutamide, thus activating an androgenic gene expression program resembling that of an AR agonist . Here we show that darolutamide remained a strong antagonist whereas enzalutamide and apalutamide had only reduced antagonist properties for these AR mutants.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, we found the AR binding motifs sequence in HCC cells were a bit different from the canonical types, and it could be attributed to the binding motif variants or tissue specificity [33, 34], which need further study. Moreover, we noticed that under the androgen stimulating, the Nanog Neg cells could turn to be Nanog Pos .…”
Section: Discussionmentioning
confidence: 99%
“…The other major phenotypic output of common LBD mutations is antagonist-agonist switching (Supplementary Table 1), which likely explains the withdrawal syndrome observed after cessation of firstgeneration antagonists seen in 15-30% of patients (Small et al 2004). T878A confers agonist properties to flutamide and nilutamide, H875Y to nilutamide and W742C/L to bicalutamide (Veldscholte et al 1990, Suzuki et al 1996, Tan et al 1997, Hara et al 2003, Azad et al 2015, O'Neill et al 2015, Lallous et al 2016. Interestingly, O'Neill and coworkers recently demonstrated that T878A inhibited bicalutamide-activated W742L (O'Neill et al 2015) in what may represent the first evidence of antagonism arising from the heterodimerization of distinct AR mutants.…”
Section: Gata2 Oct1mentioning
confidence: 99%
“…T878A confers agonist properties to flutamide and nilutamide, H875Y to nilutamide and W742C/L to bicalutamide (Veldscholte et al 1990, Suzuki et al 1996, Tan et al 1997, Hara et al 2003, Azad et al 2015, O'Neill et al 2015, Lallous et al 2016. Interestingly, O'Neill and coworkers recently demonstrated that T878A inhibited bicalutamide-activated W742L (O'Neill et al 2015) in what may represent the first evidence of antagonism arising from the heterodimerization of distinct AR mutants. Another mutation that can confer antagonist-agonist switching is F877L, which was found to be activated by enzalutamide in cell lines (Balbas et al 2013, Joseph et al 2013, Korpal et al 2013.…”
Section: Gata2 Oct1mentioning
confidence: 99%